Psychological Distress, Emotional Stability, and Emotion Regulation Moderate Dynamics of Herpes Simplex Virus Type 2 Recurrence. Issue 2 (8th October 2014) - Horn, Erin E.; Turkheimer, Eric; Strachan, Eric
Abstract: Background: Herpes simplex virus type 2 (HSV-2) genital lesion recurrence is modulated by psychological factors, but no such link with viral shedding (and thus asymptomatic transmission) has been observed in humans. Purpose: The moderating effects of average psychological distress, emotional stability, and emotion regulation on HSV-2 recurrence were tested. Methods: Nineteen HSV-2 seropositive women were followed over 22 weeks. Daily measures of HSV-2 recurrence and psychological distress were collected. HSV-2 lesions and viral shedding were modeled as linear oscillator systems, with psychological distress moderating the periodicity of each process. Results: High levels of distress, more labile moods, and less ability to regulate emotional states were associated with fewer days elapsed between the onset of lesion episodes. Viral shedding showed the same pattern. Conclusions: Results are consistent with research indicating that psychological distress suppresses immune system functioning, and provide new evidence that genital HSV-2 viral shedding is related to, and regulated by, psychological distress.